Guest Preferences And Future Challenges In The Post Covid-19 Scenario- An Exploratory Study Of Hotel Front Office Department ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background:The hospitality industry is recovering, evolving, and adapting itself in the post COVID-19 era through innovative  and sustainable practices backed by the use of technology in entire hotel operations. The hotel Front Office department is no  exception in utilizing these evolved practices to understand and influence the customer behaviour while exploring all possible  measures to enhance the overall guest stay experience in the post- COVIDtimes. The Front Office department plays a vital role  in the passage of accurate and timely information required for flawless guest management in the hotels. Throughout the  COVID-19 period, the Front Office practices have evolved through different stages depending upon the factors such as guest  preferences, safety and security measures, hygienic conditions, sustainability and use of technology. Objectives: The major  objectives are to study the post COVID-19 Hotel guest preferences of non-star category hotels with respect to changing  scenario in the Hospitality Industry, to analyse the gaps between hotel guest expectations and perceptions in service quality  with special mention of the front office department and to highlight the future challenges faced by hotel industry and suggest  possible measured to overcome these challenges. Methodology: Hybrid research approach has been adopted in this study.  Grounded theory in qualitative research approach with interview and semi-structured questionnaires are the data collection  tools. Survey method with structured questionnaire are quantitative data collection tools. Collected data were analysed through  content and thematic tools for qualitative data and quantitative data were analysed through descriptive statistics (Mean, SD,  percentage) and paired t-test as an inferential statistical tool has been applied in this study for conclusion purpose. Results: Result indicates negative as Expected value – perceived value = - (negative). Conclusion: It is concluded that hotel-guests' are  not satisfied as provided facilities are not as per guests' expectation. This study gives overview of guests' expectation. It helps  hoteliers for modification of hotel's facilities for the guest. The limitation of the study is that the study is conducted in NCR only.  Hotels of the same category in the other cities/town may be conducted for getting actual scenario of the phenomena of the  hotels. In addition, the study proposes that hotels should adjust their room and service pricing to reflect the reduced demand  during the COVID era. Furthermore, the hotel industry will face ongoing challenges, and hotels must be adaptable to remain  competitive. By embracing new technologies, providing distinctive experiences, and implementing sustainable practices,  hotels can overcome these challenges and flourish in the years ahead.
Keywords: NCR; Hotel; Guest Satisfaction; Accommodation Industry; Post- COVID; Adaptive Practices; Guest Satisfaction Guest Preferences; Safety Measures; Sustainability; Technology